2018
DOI: 10.18632/oncotarget.24077
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of early versus late closure of a temporary ileostomy after proctectomy

Abstract: Background: A temporary ileostomy is frequently constructed to reduce the risk of symptomatic anastomotic leakage. An ostomy is a heavy burden on both patient and society, and early closure is therefore desirable to counteract increased morbidity. The optimal time for stoma closure has been investigated in some studies, although it remains controversial. Methods: We conducted a literature search of PubMed, Wiley, Web of Science, and the Cochrane Library to identify studies published till 2017 that focused on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…12 Khan, et al even stated that delayed closure of ileostomy may be abandoned completely. 11 Aside from the 8 RCT's analyzed for this study, current review of literature also revealed two meta-analysis 4,15 attempting to summarize these findings. One unpublished study 4 concluded that early closure of a temporary ileostomy after proctectomy at 4 weeks shows no significantly increased morbidity, except an increased wound infection rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Khan, et al even stated that delayed closure of ileostomy may be abandoned completely. 11 Aside from the 8 RCT's analyzed for this study, current review of literature also revealed two meta-analysis 4,15 attempting to summarize these findings. One unpublished study 4 concluded that early closure of a temporary ileostomy after proctectomy at 4 weeks shows no significantly increased morbidity, except an increased wound infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…1 Gastrointestinal continuity is restored after a period of 6-12 weeks but it can be longer if the patient is on adjuvant chemotherapy or due to low priority given to this procedure. 2 It has been proven by a few RCT's 3 and one unpublished meta-analysis 4 that early stoma closure (EC) within 4 weeks after proctectomy is feasible and has some advantages in selected patients. It was also stated that early closure of a temporary ileostomy after proctectomy at 4 weeks showed no significantly increased morbidity, except for an increased wound infection rate.…”
mentioning
confidence: 99%
See 2 more Smart Citations